ANALISIS NILAI KEEKONOMIAN PERUNTUKAN LAHAN BEKAS TAMBANG BATUBARA SEBAGAI ASIMILATOR KARBON - Yovanda, Ridho; Juniah, Restu; Yulianita, Anna; Anaperta, Yoszi; Rahmi, Hisni (Balai Besar Pengujian Mineral dan Batubara tekMIRA, 2023)
The environmental issues that usually arise from mining activities are ex-coal mining lands in the form of mine pits (void) and land (non void) which are not managed properly. The company has an obligation to manage ex-coal mining land so that the environment remains sustainable and benefits the community by carrying out reclamation activities. Reclamation of ex-coal mining land by planting oil palm provides benefits in the form of incomes and as a carbon assimilator. This study aims to analyze the economics value of the ex-coal mining land use as a carbon assimilator by using the extended NPV analysis method. The result of analysis revealed a positive extended NPV value of IDR. 1,961,057,020,-, which means that ex-coal mining land can provide positive benefits as a carbon assimilator.